2012
DOI: 10.1039/c2sc00971d
|View full text |Cite
|
Sign up to set email alerts
|

Au@Pt dendrimer encapsulated nanoparticles as model electrocatalysts for comparison of experiment and theory

Abstract: In this paper we report the electrochemical synthesis of core@shell dendrimer-encapsulated nanoparticles (DENs) consisting of cores containing 147 Au atoms (Au 147 ) and Pt shells having $54 or $102 atoms (Au 147 @Pt n (n ¼ 54 or 102)). The significance of this work arises from the correlation of the experimentally determined structural and electrocatalytic properties of these particles with density functional theory (DFT) calculations. Specifically, we describe an experimental and theoretical study of Pb unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
88
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(103 citation statements)
references
References 42 publications
15
88
0
Order By: Relevance
“…and (111) facets [15]. DFT calculations indicate that Pb UPD oc-232 curs on the (100) facet before the (111) facet.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…and (111) facets [15]. DFT calculations indicate that Pb UPD oc-232 curs on the (100) facet before the (111) facet.…”
mentioning
confidence: 95%
“…[8] 57 Fig. 1 illustrates the synthetic routes to form random alloy [9,7,58 10-12], core-shell [13][14][15][16], and alloy-core@shell DENs [17]. Random 59 alloy DENs are prepared by a co-complexation method, where two 60 types of metal cations are reduced simultaneously to form an alloy par-61 ticle.…”
mentioning
confidence: 99%
“…28 Briey, a 250 mL solution of aqueous 2.0 mM Au 147 DENs was synthesized by adding 147 equivalents of HAuCl 4 to a stirred solution of 2.0 mM G6-NH 2 . Au 3+ was allowed to associate with the interior of the dendrimer for 10 min, and then a 10-fold excess of 1.0 M NaBH 4 in 0.30 M NaOH was added to reduce this precursor to Au 147 DENs.…”
Section: Synthesis Of Au Dens and Thiol-capped Au Densmentioning
confidence: 99%
“…[73] Recent results from our group showed that the GR of click dendrimer-encapsulated CuNPs with Ag + and Au 3+ yielded dendrimer-stabilized noble-metal NPs for which the catalytic reactivity in Cu-catalyzed alkyne azide cycloaddition (CuAAC) and 4-nitrophenol reduction was strongly dependent on the location of the NP in the dendrimer. [76] Very recently this research group has designed the synthesis, using GR, of polyamidoamine (PAMAM) dendrimer-encapsulated trimetallic Pd@Pt-Au nanowires, as efficient electrocatalysts for the ORR. [75] They also carried out GR of Au 147 @Pb n to replace surface Pb atoms with Pt, and density functional theory (DFT) calculations showed that oxygen-binding-involved distortions were most productive for the ORR.…”
Section: Applications Of Bi-and Multimetallic Nanomaterials Synthesizmentioning
confidence: 99%